Cytochemical findings in pleural fluid from patients with COVID-19, cared for in an emergency department - Quispe-Aranda, David (2021)
Objetive: The purpose of this work was to describe the physical, cytological and biochemical characteristics, as well as to classify the pleural fluids of patients with COVID-19 as exudates or transudates. Material and Methods: An observational, descriptive cross-sectional study was carried out. Data was collected from the cytochemical examination of pleural fluid samples processed between the months of April to September 2020, in the laboratory of the Emergency Center of Metropolitan Lima (CELIM). Results: During the study period, a total of 81 samples of pleural fluid from patients with COVID-19 were evaluated, of these, 26 met our eligibility criteria. Fourteen liquids (54%) had a red color and 18 (69%) had a cloudy appearance. Exudative pleural fluids were the majority (n = 17), total proteins presented a mean of 3.3 g / dl (SD: 1.5), LDH a median of 544 U / L (IQR: 262-2016), the leukocyte count had a median of 610 leukocytes / ul (IQR: 180-968) and the differential polymorphonuclear count a median 29% (IQR: 15-60). Regarding the clinical characteristics, of the total exudates, 41% corresponded to neoplasms and 23% to pneumonia. While, of the total transudates (n = 9), 45% came from patients with neoplasms. Conclusions: In our study we observed that most of the pleural fluid samples from patients with COVID-19 were classified as exudates. These presented a low differential leukocyte percentage of polymorphonuclear cells. The values ​​of the biochemical parameters such as total proteins and LDH were adequately related to the classification of exudates